2020
DOI: 10.1186/s13020-020-00390-2
|View full text |Cite
|
Sign up to set email alerts
|

Trilobatin ameliorates insulin resistance through IRS-AKT-GLUT4 signaling pathway in C2C12 myotubes and ob/ob mice

Abstract: Background Trilobatin, a natural compound, has been found to exhibit anti-diabetic properties in high-fat diet (HFD) and streptozotocin (STZ) induced type 2 diabetic mice. But up to now no research has been reported on the effect of trilobatin on insulin resistance in peripheral tissues. Herein, we determined the effects of trilobatin on insulin resistance in palmitate-treated C2C12 myotubes and ob/ob mice. Methods Male ob/ob mice (8-10 weeks) and same background C57BL/6 mice were used to evaluate the role o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
(53 reference statements)
4
8
0
Order By: Relevance
“…Although how trilobatin regulates the expression of miR-375 is still not fully understood, together with our previous nding that trilobatin improved insulin resistance in skeletal muscle of ob/ob mice [11], the results of the current study suggested that trilobatin might be a promising lead compound for the management of metabolic syndrome because of its anti-in ammatory activity. a and b: After the differentiated 3T3-L1 adipocytes were preincubated with 1 µg/mL LPS for 8 h, the indicated concentrations of trilobatin (Tri) were added and continued to incubate 24 h. The mRNA and protein levels of FABP4 were determined with qRT-PCR and western blot assays.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although how trilobatin regulates the expression of miR-375 is still not fully understood, together with our previous nding that trilobatin improved insulin resistance in skeletal muscle of ob/ob mice [11], the results of the current study suggested that trilobatin might be a promising lead compound for the management of metabolic syndrome because of its anti-in ammatory activity. a and b: After the differentiated 3T3-L1 adipocytes were preincubated with 1 µg/mL LPS for 8 h, the indicated concentrations of trilobatin (Tri) were added and continued to incubate 24 h. The mRNA and protein levels of FABP4 were determined with qRT-PCR and western blot assays.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, trilobatin had been reported to decrease cerebral ischemia/reperfusion-induced neuroin ammation and oxidative injury via suppressing Toll-like receptor 4 (TLR4)/nuclear factor-kappa B and Nrf2/Kelch-like ECH-associated protein 1 (Keap-1) signaling pathways in vitro and in vivo [10]. Our previous works demonstrated that trilobatin ameliorated insulin resistance and improved the expression and translocation of glucose transporter 4 (GLUT4) via insulin receptor substrates (IRS)/ phosphatidylinositol 3 kinase (PI3K) signaling pathway in C2C12 myotubes and the muscle tissues of ob/ob mice [11]. However, the effect of trilobatin on adipose tissues of obesity and the mechanisms of actions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 21 studies in English and Chinese including 320–332 animals were included. 11–31 The whole process was shown as a flow chart (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, TLB is also used as a natural food additive with high sweetness but low calories and displays an anti-DM effect on high-fat diet (HFD) or streptozotocin-induced DM mice (Wang et al, 2016). Moreover, it also improves insulin resistance in ob/ob mice by activating the insulin receptor substrate (IRS)/protein kinase B (Akt)/ glucose transporter-4 (GLUT-4) signaling pathway (Liu et al, 2020). Interestingly, our previous studies demonstrated that TLB exerts predominant neuroprotective effects due to its striking antioxidative profile (Gao et al, 2020;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%